2018
DOI: 10.1177/0829573518793752
|View full text |Cite
|
Sign up to set email alerts
|

Should I Defend or Should I Go? An Adaptive, Qualitative Examination of the Personal Costs and Benefits Associated With Bullying Intervention

Abstract: Bystanders play a crucial role in encouraging or preventing bullying situations and feature prominently in several international antibullying programs (e.g., KiVa). Despite a surge of recent interest in bystanders, relatively little is known about the functional reasons why individuals choose to engage with or ignore bullying incidents. Given the importance of bystanders’ influence on bullying, we argue that further consideration needs to be given to the individual costs and benefits of bystanders’ interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…It has been proposed that bullies may use their peer status to punish defenders who hinder their bullying (Juvonen & Galván, 2008) as it has been found that defenders become less liked by their peers over time (Meter & Card, 2015). Because of the anticipated costs of defending, several researchers proposed that some students may be less willing to intervene because they may be afraid to become the next target of bullying or to lose peer status (Pöyhönen, Juvonen, & Salmivalli, 2010;Pronk, Goossens, Olthof, de Mey, & Willemen, 2013;Salmivalli, 2010;Spadafora, Marini, & Volk, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that bullies may use their peer status to punish defenders who hinder their bullying (Juvonen & Galván, 2008) as it has been found that defenders become less liked by their peers over time (Meter & Card, 2015). Because of the anticipated costs of defending, several researchers proposed that some students may be less willing to intervene because they may be afraid to become the next target of bullying or to lose peer status (Pöyhönen, Juvonen, & Salmivalli, 2010;Pronk, Goossens, Olthof, de Mey, & Willemen, 2013;Salmivalli, 2010;Spadafora, Marini, & Volk, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as the HEXACO model is grounded within social evolution theory (Ashton & Lee, 2007; De Vries et al, 2016), personality predictions can be made that complement the contemporary views within the bullying research field. Evidence is mounting that bullying, and to a lesser extent defending, are types of adaptive behavior that can strategically help adolescents to optimize their peer‐group status (e.g., Olthof et al, 2011; Pronk et al, 2017, 2019; Reijntjes et al, 2013; Spadafora et al, 2020; Vaillancourt et al, 2003; Volk et al, 2014). Two status dimensions are important.…”
Section: Predicting Adolescents' Involvement In Bullying With the Hexacomentioning
confidence: 99%
“…Defending was found to reward adolescents with prestige over time, at least in terms of social preference (i.e., being liked; Pronk et al, 2020) and has been associated with altruistic behavioral strategy use (Pronk et al, 2019). Moreover, Spadafora et al (2020) recently found that one of motives underlying the decision to defend peers concerns the peer‐group status benefits for the individual. Taken together, these studies suggest that adolescents strategically use defending to get along with others and to create peer‐group cohesion.…”
Section: Predicting Adolescents' Involvement In Bullying With the Hexacomentioning
confidence: 99%
“…In a longitudinal study, van der Ploeg, Kretschmer, Salmivalli, and Veenstra (2017) found that a higher level of affective empathy and self-efficacy predicted defending behaviour. Children have been found to be quite aware of the benefits and costs of intervening in bullying situations ( Spadafora, Marini, & Volk, 2020 ); costs included getting into trouble, loss of friends, loss of popularity, and becoming a target themselves. Our findings indicate that similar costs may be perceived by university students.…”
Section: Discussionmentioning
confidence: 99%